The influence of students' beliefs on their speaking performance = tác động của niềm tin đối với khả năng nói của sinh viên. M.A. Thesis Linguistics: 60 14 10 - Trần, Thị Miên Viễn (ĐHNN, 2017)
35 p. + CD-ROM